Идејата и потребитоста од етика на грижата како етика на одговорноста - Донев, Дејан (Правен факултет „Јустинијан I“, Скопје, 2013)
Each man, if it wants to have a better and quality life, must take care for it, meaning that it is necessary to have more caring concentration in resolving the problems; having care which presents focusing on duties to be realized as it should be. In contemporary world, this care for general hard problems and for the damnation of all people, showed female ethicians, between which the first one is Carol Gilligan, developing a new kind of ethics - ethics of care, which emphasizes the fact that man must change from violence and not taking care, toward love and caring, like mothers that takes care and holding their children. In another words, toward ethics of care as an ethics of responsibility, an ethics that promises that there will be no more violent acting that will hurt Nature and all living beings.
The idea and need of ethics of care as an ethics of responsibility
Годишник на Правниот факлтет „Јустинијан Први“ Том 49, во чест на Љиљана Спировиќ-Трпеновска
Keywords: care, responsibility, ethics of care, living beings